International Trade Driven Growth Patterns in India, Pakistan, and Sri Lanka (1985 - 2015) : An Empirical Study - Tripti,; Bandyopadhyay, Gargi (Indian Journal of Finance, 2017)
The purpose of this study was to conduct a comparative analysis of the Marshall - Lerner condition in case of India, Pakistan, and Sri Lanka for the time period from 1985 - 2015. Also, the paper attempted to show an empirical verification of the Marshall - Lerner condition. As the recession is prominent in the developed and the developing countries, therefore, this condition can provide respite in the form of a path to be followed to arrest recession. In order to analyze this condition, five variables were taken in this study namely; exports, imports, GNI, exchange rate, and world income. The annual data were collected from the World Bank database. All these variables were tested for stationarity and then for cointegration via SAS and finally, OLS technique was applied in order to find the import and export elasticity. The condition was tested separately for India, Pakistan, and Sri Lanka and then the comparisons were drawn. The results showed that this condition was satisfied in all three countries, but there were still certain important differences in the scenarios in the countries which led to the justification of the Marshall-Lerner condition. All these findings were supported with empirical analysis using available data. This study will be helpful to determine the trends in trade, and future research can be done to suggest the various changes which will help our country to grow its international trade.